From Words to Acts: Speech Act Analysis of Presidential Concessions in Ghana - Afadzie, Samuel; Yedu, Rita (JEE (Journal of English Education), 2024)
When people communicate via language, the listeners obtain a comprehension of the speaker's intentions. The purpose of this study was to examine the many sorts of illocutionary behaviours observed in concession speeches. The data was the concession speech of the two presidential candidates which were retrieved online. The study was a qualitative study backed by quantitative methodology. The data was analysed by categorising it using Searle's categorization of speech activities. Each category was thoroughly observed to find the illocutionary act and the illocutionary force associated with the utterance. It was realized that Nana Akufo Addo's assertives accounted for 31%, while John Mahama's assertives accounted for 46%. In terms of directives, Nana Akufo Addo delivered more directive act than John Mahama. Nana Akkufo Addo performed one commissive act, accounting for 3% of the total. Meanwhile, John Mahama performed 2 (5%) commissive acts. This act was the least common of the five acts. Expressive act accounted for the most illocutionary act in Nana Akufo Addo's speech, while it accounted for the second most in John Mahama's speech. Nana Akufo Addo made 4 declarative, while John Mahama made 2. The study is significant to theory and practice.